INOVASI KURIKULUM SEKOLAH INKLUSI DALAM PENGUATAN LITERASI BACA-TULIS: MEWUJUDKAN AKSES PENDIDIKAN BERKUALITAS YANG SETARA - Siti Raihan; Nurhaedah; Amir Pada; Awayundu Said; Yulia Asta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Inclusive education in elementary schools aims to provide equal access for all students, including those with special needs. One of the main challenges in implementing inclusive education is strengthening literacy skills, which are essential for academic success. This study aims to identify and analyze the curriculum innovations implemented in inclusive elementary schools to strengthen literacy skills. A qualitative descriptive approach with a case study design was used in this research. The study was conducted in two inclusive elementary schools in Makassar City that apply the Merdeka Curriculum. The subjects of the study consisted of school principals, classroom teachers, special education teachers (GPK), and both special needs and regular students. Data were collected through observations, interviews, and document analysis. The results showed that curriculum innovations, such as the use of Universal Design for Learning (UDL) principles, project-based learning, and the integration of educational technology, significantly supported the strengthening of literacy skills. Moreover, collaboration among teachers, students, parents, and the community played a key role in creating an inclusive and literate learning environment. This study concludes that responsive curriculum innovations that cater to the individual needs of students are crucial in achieving equitable and inclusive education in elementary schools.